Identifying the presence of magnetite in an ensemble of iron-oxide nanoparticles: a comparative neutron diffraction study between bulk and nanoscale. Issue 12 (28th April 2021) - González-Alonso, D.; Espeso, J. I.; Gavilán, H.; Zeng, L. J.; Fernández-Díaz, M. T.; Subías, G.; de Pedro, I.; Fernández, J. Rodríguez; Bender, P.; Barquín, L. Fernández; Johansson, C.
Abstract : We exploit the Verwey transition to detect the presence of magnetite in an ensemble of IONPs by using the thermal evolution value of the magnetic moment obtained by neutron diffraction in a mixture of maghemite and magnetite phases in their cores. Abstract : Scientific interest in iron-oxides and in particular magnetite has been renewed due to the broad scope of their fascinating properties, which are finding applications in electronics and biomedicine. Specifically, iron oxide nanoparticles (IONPs) are gathering attraction in biomedicine. Their cores are usually constituted by a mixture of maghemite and magnetite phases. In view of this, to fine-tune the properties of an ensemble of IONPs towards their applications, it is essential to enhance mass fabrication processes towards the production of monodisperse IONPs with controlled size, shape, and stoichiometry. We exploit the vacancy sensitivity of the Verwey transition to detect the presence of magnetite. Here we provide direct evidence for the Verwey transition in an ensemble of IONPs through neutron diffraction. This transition is observed as a variation in the Fe magnetic moment at octahedral sites and, in turn, gives rise to a change of the net magnetic moment. Finally, we show this variation as the microscopic ingredient driving the characteristic kink that hallmarks the Verwey transition in thermal variation of magnetization.